Petrology and geochemistry of sheeted dykes and pillow lavas from the Sabzevar Ophiolitic Mélange (Northeast Iran): new Constraints for the Late Cretaceous evolution of the Neo-Tethys Oceanic Basin between the Central Iranian Microcontinent and Eurasia - Rezaei, Zahra; Noghreyan, Moussa; saccani, Emilio (Ofioliti, 2018)
TheSabzevarophiolite-bearingmélangemainlyincludestectonic slicesofophiolitesregardedas remnants of the Late Cretaceous oceanic basin located between the northern margin of the Central Iran Microcontinent and the southern margin of the Turan (Eurasia) plate, as well as remnants of its northern continental margin. We present here new mineral chemistry and whole rock chemical data on the sheeted dyke complex and pillow lavas series from this ophiolite. The sheeted dykes consist of basalts and basaltic andesites showing island arc tholeiitic (IAT) affinity (Group 1). They display low TiO2(0.37-0.81 wt%) contents and N-MORB normalized incompatible element patterns featuring Th enrichment and Ta and Nb depletion. The pillow lavas show different chemical features compared to the sheeted dykes and can be subdivided in two distinct geochemical groups. The first Group of pillow lavas (Group 2) mainly consists of andesites showing a clear calc-alkaline (CA) affinity with low TiO2(0.71-0.81 wt%) contents. Their N-MORB normalized incompatible element patterns display marked enrichments in Th, U, La, and Ce, and depletion in Ta, Nb, and Ti. The second Group of pillow lavas (Group 3) is mainly represented by alkaline basalts with high TiO2(1.54-3.45 wt%) contents. N-MORB normalized incompatible element patterns show significant Th, Ta, and Nb enrichments. Trace element modeling shows that CA primary melts were generated by 20% partial melting of a depleted lherzolite mantle source that had been enriched by continental crust chemical components. IAT basalts were generated from various degrees of partial melting of either depleted lherzolitic or harzburgitic mantle sources bearing no or negligible influence from continental crust components. Alkaline basalts were generated by polybaric partial melting of an enriched within-plate oceanic mantle source. A new tectono-magmatic model that can explain the different rock association cropping out in the Sabzevar ophiolite is proposed. This model implies the existence, on the southern margin of the Turan plate during the Late Cretaceous, of a continental arc-forearc system where CA and IAT rocks were erupted, respectively. Alkaline basalts were erupted in a subduction-unrelated oceanic basin and then tectonically accreted to the forearc as a consequence of the collision between the seamount and the arc-forearc system.